Autum festivals - Rosen, Mike (Wayland Hove, 1990)
The book Autumn Festivals by Mike Rosen, published in 1990 by Hodder Wayland. This 32-page hardcover is part of the "Seasonal Festivals" series and explores various religious and secular celebrations that occur during the autumn season. It covers international festivals such as the Festival of Kali, Rosh Hashanah, Diwali, Thanksgiving, and various tropical harvest festivals. The book is illustrated with color photographs and artwork throughout, providing readers with a visual understanding of these diverse cultural events.